Efektivitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Kabupaten Klaten Pada Bencana Banjir Dengan Menggunakan Strategi Make A Match Terhadap Hasil Belajar Siswa Di Smk Negeri 1 Trucuk - Puspitaningrum, Oktavia Ayu; , Dra. Siti Taurat Aly, M.Pd (2016)
This study aims to determine the effectiveness of teaching materials on disaster learning guide books Klaten district in the flood disaster by using the strategy of Make A Match at SMK Negeri 1 Trucuk. This research uses quasi xperimental research. Popupasi in this study were students of class X that follows ektrakurikuler Disaster Alert School (SSB). SMK Negeri 1 Trucuk. Samples from this study two classes A and B, the experimental class to class A using the Make A Match learning strategies and the control class to class B using conventional pembelajarn strategy. The sampling technique sampling saturated. Date collection techniques by testing, observation and documentation. The results obtained from views of value - average post-test. In the experimental group obtained the results of the post test average of 82.91, while the control class earned an average value of post test of 79.79. Each classroom has a qualified KKM 78 but for the control class nearing the KKM. This study also uses Wilxocon test and Mann-Whitney test values obtained Wilxocon probability of 0.000 and 0.015 Mann-Whitney, so that there is an influence and a significant difference between the control group and the experimental class thus Ho is rejected and Ha accepted.